(untitled) (Global Journals of Research in Engineering, 2014)
A renewed interest in vertical axis wind turbines (VAWT) has been seen recently, in particular at relatively low Reynolds number (Rec #x2248; 10 5 ) appropriate to the urban applications. From this perspective, the Computational Fluid Dynamics (CFD) is regarded as a promising technique for aerodynamic studies of VAWT. The paper presents a computational investigation on a particular dynamic stall phenomenon associated with unsteady flow around the NACA 0018 a irfoil o f a t hree s traight b laded rotor, a t h igh a ngle o f attack (AOA). Two airfoil flows with angle of attack higher than 45o of an isolated blade and a confined blade in rotor at low speed ratios (TSR), are numerically simulated using CFD. It is concluded that the quasi-steady prediction used in previous models is in disagreement with experimental and numerical data because the unsteadiness generated by spinning rotor, though very important for the self-starting of VAWT, in the past were ignored.